Synthesis, characterization and photoluminescence properties of CdTe nanocrystals - T. Suriwong (2018)
© 2015, Virtual Institute of Physics of the Foundation Horia Hulubei. All rights reserved. Cadmium telluride (CdTe) nanocrystals were solvothermally synthesized using Cd(NO3)2-4H2O and Te powder in ethylenediamine (C2H4(NH2)2) at 200°C for 12-72 h. Phase, morphology and photoluminescence (PL) property of the products were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and photoluminescence spectroscopy. The product synthesized at 200°C for 72 h was specified as cubic CdTe nanocrystals (41.39 nm) evaluated by the Scherrer equation, with 550 nm emission peak excited by 300 nm wavelength.